(v-2)(5v-3)=o

Simple and best practice solution for (v-2)(5v-3)=o equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-2)(5v-3)=o equation:


Simplifying
(v + -2)(5v + -3) = o

Reorder the terms:
(-2 + v)(5v + -3) = o

Reorder the terms:
(-2 + v)(-3 + 5v) = o

Multiply (-2 + v) * (-3 + 5v)
(-2(-3 + 5v) + v(-3 + 5v)) = o
((-3 * -2 + 5v * -2) + v(-3 + 5v)) = o
((6 + -10v) + v(-3 + 5v)) = o
(6 + -10v + (-3 * v + 5v * v)) = o
(6 + -10v + (-3v + 5v2)) = o

Combine like terms: -10v + -3v = -13v
(6 + -13v + 5v2) = o

Solving
6 + -13v + 5v2 = o

Solving for variable 'v'.

Reorder the terms:
6 + -1o + -13v + 5v2 = o + -1o

Combine like terms: o + -1o = 0
6 + -1o + -13v + 5v2 = 0

The solution to this equation could not be determined.

See similar equations:

| 9-8x+16x-9=-56 | | 6x^3+7x^2-30x+9=0 | | 4(y)=215-y | | 1.5n-3=6 | | 26=36-2-76 | | -3x^2-30x=18 | | X+(x-1)=12 | | ln(x+3)=11 | | x^2=-4x+1 | | 3p-7=12 | | (a-3)(a+5)=0 | | (h+3h)-(5h+11h)= | | x^2-7x-64=0 | | h+3h-5h+11h= | | x^2-12=8x | | 2a-b=24 | | (x+3)(5x-7)=0 | | 18+2p=-13 | | -21-x+5+2x=-46 | | 5y-20=4y | | f(x)=3x^3-9x^2+3x+2 | | 3x*2-28=20 | | 11f-(-2f+2)= | | -8+8g= | | 4t*2-36=0 | | a+2b+3c+4d+5e+6f+7g+8h+9i+10j=1000 | | -3x-8x=121 | | 2x+30=y | | 3.5x+2y=120 | | m+5=m-3whatism | | x^2+7=52 | | 5x+1/8=6x+7/8 |

Equations solver categories